Effectiveness of the mushroom technique versus morcellation in en bloc bipolar prostate enucleation for prostates over 80 mL - Zoltán Kiss; Mihály Murányi; Attila Nagy; Tibor Flaskó (PLoS ONE, 2025)
Background and objectives Anatomical endoscopic enucleation of the prostate (AEEP) has revolutionized the surgical treatment of benign prostatic hyperplasia, offering advantages over transurethral prostate resection (TURP). This study aimed to compare the effectiveness of the mushroom technique versus morcellation in en bloc transurethral bipolar prostate enucleation (TUEB) for prostates > 80 mL, hypothesizing that morcellation would reduce operative time. Patients and methods We retrospectively reviewed 234 TUEB procedures performed between January 2018 and March 2024 at a tertiary university hospital. Patients were divided into two groups: the mushroom technique group (n = 116) and the morcellation group (n = 118). Demographic and clinical data were collected and outcomes, such as operative time, efficacy, and complications, were analyzed. Results The median operative time was significantly longer in the mushroom cohort (80 [60–90] min) than in the morcellation cohort (60 [50–70] min) (p < 0.001). Efficacy, which was measured in g/min, was higher in the morcellation group (1.25 [1.01–1.44] g/min) than in the mushroom group (0.9 [0.76–1.03] g/min) (p < 0.001). Linear regression analysis showed that the prostate volume significantly influenced the operative time of the mushroom technique more than that of the morcellation technique. Complications were similar across the groups, with no need for blood transfusion or conversion to TURP. Conclusions Morcellation is an efficient method for tissue removal during bipolar prostate enucleation particularly for larger prostates, owing to its shorter operative time and consistent efficacy. Although the mushroom technique is a viable alternative, it is less efficient for larger glands. Nevertheless, both techniques demonstrated similar safety profiles and functional outcomes. Further multicenter trials are required to confirm these findings.